Nanobore PCF maintaining cylindrically polarized modes - Euser, T. G.; Joly, N. Y.; Gabriel, C.; Marquardt, Christoph; Zang, L. Y.; Banzer, P.; Brenn, A.; Elser, D.; Förtsch, M.; Rammler, S.; Scharrer, M.; Leuchs, Gerd; et al. (Optics InfoBase Conference Papers, 2010)
A nanoscale hole placed centrally in the core of a PCF breaks the degeneracy between radially and azimuthally polarized modes, causing a large splitting in phase velocity, group velocity and dispersion. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05